Fungal Frequency and Diversity in the Nests of Wetland Birds from Poland: Relationships between Birds, Nest Properties and Inhabiting Fungi. (October 2018) - Korniłłowicz-Kowalska, Teresa; Kitowski, Ignacy; Bohacz, Justyna; Kwiatkowska, Edyta
Avian nests are a unique and sometimes extreme environment in which fungi occur. In this study, a correlation was recorded between the breeding biology and ecology of wetland birds and the biology and ecology of fungi in nests of wetland birds. The abundance of ecophysiologically diversified fungi, i.e. saprotrophs, cellulolytic fungi, and potentially zoo- and phytopathogenic fungi, was shown to be significantly higher in large nests, while species diversity (Shannon index) of fungi in nests with similar properties was not significant. The taxonomic structure (genus and species composition) and the spatial structure (frequency) of the nest mycobiota are mainly affected by nests' specific physical and chemical properties which depend on the breeding and feeding preferences of the birds. In dry, highly sun-exposed nests of the Grey Heron (Ardea cinerea), a species that establishes breeding colonies high in the trees, mainly feeds on fish and has young who defecate into the nest, populations of xerophilic, alkali- and thermotolerant fungi, including keratinolytic fungi (Chrysosporium tropicum), developed. In the nests of the Mute Swan (Cygnus olor), a precocial species which constructs very large, relatively low-hygiene nests at the water's edge and which feeds on plant food, populations of hydrophilic and thermotolerant fungi, including highly cellulolytic fungi such as Chaetomium globosum, were detected. Nests of other small species of wetland birds, whose nests are also located on water but contain smaller amounts of animal-derived material, did not differ significantly mycologically and were colonised mainly by species such as Trichoderma viride and Penicillium purpurogenum, ubiquitous fungi with very high water and thermotolerant requirements.